2017
DOI: 10.3390/su9091638
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Cost Analysis of Incineration and Recovery Alternatives for Flammable Industrial Waste: The Case of South Korea

Abstract: Abstract:As the generation of industrial wastes increases, waste treatment is steadily becoming a serious economic and environmental issue. Existing waste has mainly been treated by landfilling after incineration. A shortage of landfill sites necessitates waste management alternatives other than traditional incineration and landfill. This paper focuses on a cost-benefit analysis that evaluates the economic and environmental performances of five treatment strategies for flammable industrial wastes: incineration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
(17 reference statements)
0
12
0
3
Order By: Relevance
“…Only the final treatment is involved in the treatment of the toxic and harmful substances in the sludge. The common harmless processes in this step include composting, landfill, incineration, , pyrolysis, and hydrothermal treatment (HT). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the final treatment is involved in the treatment of the toxic and harmful substances in the sludge. The common harmless processes in this step include composting, landfill, incineration, , pyrolysis, and hydrothermal treatment (HT). …”
Section: Introductionmentioning
confidence: 99%
“…Only the final treatment is involved in the treatment of the toxic and harmful substances in the sludge. The common harmless processes in this step include composting, 7 landfill, 8−10 incineration, 11,12 pyrolysis, 13 and hydrothermal treatment (HT). 14−16 Composting is a method that can utilize the different nutrients in sludge, such as N, P, and K. This technique not only satisfies the harmlessness criterion, but also recycles the resources.…”
Section: Introductionmentioning
confidence: 99%
“…Between the two pre-treatment methods used in this study, microwave irradiation was more economically efficient than incineration. Past studies on cost analyses reported values of around USD 0.12/kg and 0.17/kg for microwave irradiation and incineration pre-treatments, respectively [28,29]. However, further studies on detailed economic analysis with a preferred focus on recovery and pre-treatment cost, social costs reduction for environmental protection, and pollution prevention need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The high capital cost of incineration plants is justified by restricted environmental design and environmental emission regulations. Incineration plants require cost upgrades including particulate matter removal, semi-dry and wet scrubbers for acidic gases, selective non-catalytic and catalytic reduction in nitrous oxides (NOx), and activated carbon (AC) technology for removal of dioxins and heavy metals [46][47][48][49][50][51]. The equipment installed to reduce greenhouse gaseous emissions are considered CAPEX, whereas day to day operational equipment such as filters and removal of acidity in effluent gases are considered OPEX.…”
Section: Techno-economic Assessment Of Thermochemical Processesmentioning
confidence: 99%
“…Incineration chemical plants require NOx and SOx combustors to ensure complete combustion and reduce overall harmful emissions. Moreover, activated carbon (AC) is used to remove chlorine, particles, and volatile organic compounds (VOC) from gaseous effluents [50,53].…”
Section: Techno-economic Assessment Of Thermochemical Processesmentioning
confidence: 99%